Bolstering Societal Resilience: The Crucial Role of Ukraine’s Territorial Defence Forces in Safeguarding the Nation - Bohatyrets, Valentyna; Zoriy, Yaroslav (Naukowa/scientific editing: Tadeusz Zieliński, Leszek Elak, Sławomir Żurawski, Zbigniew Ciekanowski Warszawa-Chełm, 2023)
It should be articulated that in the context of unprovoked russo-Ukrainian asymmetric war, Territorial Defence Forces proved to have played a vital role in bolstering societal resilience by safeguarding the security and stability of a nation. Consequently, Ukraine’s TDF’s top priority is to protect the territorial integrity of our country, defend its borders, and ensure the safety of Ukraine’s citizens. The current reality provided solid evidence that TDF’s role extends beyond traditional military operations, since they actively contribute to the resilience of our society in various ways. The authors’ focus revolves around the pivotal role of Ukraine’s Territorial Defence Forces (TDF) in enhancing societal resilience within the country. Amidst historical conflicts and ongoing security threats, the TDF has emerged as a vital component of Ukraine’s defence strategy. The present study has been developed in two stages and makes use of qualitative methods. This article delves into the structure and functions of territorial defence forces, emphasising their contributions to local security, rapid response, crisis management, national unity, and community resilience. By actively engaging citizens in defence efforts and providing comprehensive training and support, the TDF strengthens the bond between the state and its people, fostering a shared responsibility for national security. Through their presence within communities, territorial defence forces instil a sense of reassurance and resilience, enhancing the morale and confidence of the civilian population. Moreover, TDF units serve as a rapid response force, equipped to address emerging threats and crises promptly. The collaboration between territorial defence forces and local law enforcement agencies enables effective coordination in maintaining public order and combating crime. By building resilience at the community level through preparedness initiatives, the TDF empowers civilians with the necessary skills and knowledge to respond effectively to hybrid threats and various challenges/ Embracing and highlighting the pivotal role of territorial defence forces is crucial for Ukraine’s ongoing efforts to bolster societal resilience in the face of russia’s aggression and internal uncertainties.
Chapter of the Monograph "Odporność społeczeństwa (państwa) na zagrożenia hybrydowe/ENG: Society (state) resistance to hybrid threats"
Keywords: hybrid threats; local security; national unity; societal resilience; Territorial Defence Forces; unprovoked russo-Ukrainian war